IMPROVING AND MANAGING HUMAN RESOURCES MANAGEMENT BY IMPLEMENTING APPLICATIONS FOR EMPLOYEE DATA WITH WEBSITES - Raihansa Romadhon; Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to explore the application of a website-based personnel data information system as a strategy for improving and managing human resource management (HR) effectively. The research method used is descriptive analysis and case studies of organizations that have implemented this information system. The research results show that implementation of a website-based personnel data information system makes a positive contribution in increasing efficiency in the HR management process, facilitating better data accessibility, and supporting more timely and data-based decision making. The implication of these findings is the use of technology in HR management can be an effective strategy, increase productivity and achieve better business goals